CHALLENGES IN THE TRANSLATION OF LEGAL TERMS IN ENGLISH AND UZBEK (Ustozlar uchun, 2026)
This article examines the main challenges in translating legal terms between English and Uzbek. Legal translation is considered one of the most complex types of professional translation because it requires knowledge of language, law, and cultural context. The study applies comparative and descriptive methods to analyze legal terminology in both languages and identify different types of equivalence, including full, partial, functional, and zero equivalence. The research highlights that differences between the Common Law system of English-speaking countries and the Civil Law system of Uzbekistan create serious translation difficulties. Particular attention is given to nationally specific terms such as mahalla and Oliy Majlis, which require descriptive translation or transliteration. The article also discusses effective translation strategies such as borrowing, adaptation, contextual explanation, and syntactic transformation. It is concluded that successful legal translation requires not only linguistic competence but also professional legal knowledge and deep understanding of both legal systems.